Antioxidant Activity Test of Ethanol Extract of White Ginger (Zingiber officinale var amarum) Using DPPH Method - Nurani Hasanela; Catherina Manukpadang Bijang (Biofaal Journal, 2025)
Antioxidants are substances that can delay, slow down, and prevent the oxidation process caused by free radicals. The aim of this research is to determine the phytochemical content and antioxidant activity of fresh white ginger and ginger powder (Zingiber officinale Rosc.) using the DPPH method. Fresh white ginger and ginger powder were extracted using the maceration method with ethanol as the solvent. The yield obtained for the ethanol extract of fresh white ginger was 70.042%. Meanwhile, the ethanol extract of ginger powder yielded 59.984%. Phytochemical test results for the ethanol extracts of fresh white ginger and ginger powder showed positive results for flavonoids, phenolics, and saponins, while steroids yielded negative results. In the determination of antioxidant activity, a UV-Vis spectrophotometer was used with the DPPH method. The antioxidant activity test on the ethanol extract of fresh white ginger yielded an IC50 value of 19.85 ppm, while the ginger powder extract showed an IC50 value of 31.58 ppm.